Pengaruh Karakteristik Wirausaha Terhadap Keberhasilan Usaha Industri Kerajinan Tulang di Desa Tampaksiring Kabupaten Gianyar - Ni Kadek Juliantari; Kadek Rai Suwena (Ekuitas: Jurnal Pendidikan Ekonomi, 2023)
This study was conducted with the aim of knowing how entrepreneurial characteristics, the influence of entrepreneurial characteristics and business sustainability in the bone craft industry in Tampaksiring Village, Gianyar Regency. The research conducted falls into the type of causality research and as many as 50 respondents as a sample determined by saturated sample technique. In analyzing the data used simple linear regression analysis techniques, t test hypothesis test and determination coefficient test with a questionnaire as an instrument. This study shows the results that the success of a business is greatly influenced by the characteristics of the entrepreneur himself. This is stated that variable X has a value of 0.528 in the results of the simple regression analysis carried out, meaning that variable Y will increase if variable x also increases. The significance value of the t test is 0.000, the value is smaller than 0.05, which means Ha is accepted. The coefficient of determination R2 the results shown are 0.586, meaning that business success (Y) is strongly influenced by entrepreneurial characteristics (X) by 58.6% while other variables affect the rest.